ANALISIS PERKUATAN TANAH DASAR PADA TANGGUL SUNGAI GAJAH PUTIH SURAKARTA DENGAN CERUCUK KAYU - Ridwan Hermawan; Niken Silmi Surjandari; Sholihin As'ad (Matriks Teknik Sipil, 2014)
Local Government of Surakarta has implemented treatment program for retaining wall that collapse in eastern Tempurejo Bridge, Sumber,Banjarsari. The cause is base course including the soft soil which can be caused by former squatters wells, and added by vegetation that make thesoil more friable. The other cause is many people use it to access the vehicles, including heavy vehicles that take minerals from Gajah Putih Riverresulted heavy loads for retaining wall and base course. This condition continue to the soil support capacity failure of retaining wall. DPUSurakarta use wood pile as treatment solution to repairing base course for raising the soil support capacity. Wood pile can be analogous to a shortpile, this is type foundation that widely used in soft soil, especially for support a heavy loads. So the researcher did an analysis on wood pile to findthe value of safety factor (SF) from retaning wall stability and wood pile stability with various ground water level. Futhermore, to find the effect forvarious wood pile configuration that is piles length and space between piles which used in group pile to get the optimum configuration. The analysisof manual calculation used Hansen, Rankine and Terzaghi methods.The analysis result shown that retaining wall lacks of shear stability and soilsupport capacity to withstand the internal dead load and external life load. By using wood pile the shear stability and soil support capacity hasincreased. Increment length of piles gave increasing of soil support capacity and lateral force resistance. In the other way, increment space betweenpiles gave decreasing of soil support capacity. From analysis result in various configuration, 7L 2,5d is the configuration that generates theoptimum safety factor which mean group pile used 7m length and space between piles used 2,5d where d is 0,2m.